R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the National Academy of Sciences of Ukraine: 25 years with the OECI (PH Akademperiodyka, 2023)
It was in 1994 when R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the National Academy of Sciences of Ukraine (IEPOR) became a member of the Organisation of European Cancer Institutes (OECI) — a non-governmental, non-profit legal entity established in 1979 to promote greater cooperation among European Cancer Centres and Institutes. The basic aim of the Organisation is “promoting efficient partnership across Europe, notwithstanding its linguistic barriers and traditional care and research heterogeneity”. All these 25 years, IEPOR takes an active part in different OECI activities, including translational research in oncology, molecular pathology, education and training, etc. Annually the OECI holds General Assemblies along with relevant scientific conferences during OECI Oncology Days. IEPOR actively participates in these events either making presentations or taking part in Round Tables and Panel discussions. The participation of IEPOR Director in these events provides real opportunities for “synchronizing watches” in issues of modern European trends in scientific research in the field of oncology. The Institute’s active position in the OECI activities contributes to the increase of the scientific research level and comprehensive inclusion in the European oncology scientific space. Nowadays, the OECI is a network of 93 members who are collaborating to reduce fragmentation and to give to all European cancer patients the possibility of receiving the best available care. The detailed information on the OECI is available on the official website: www.oeci.eu. After more than 40 years of its activity, the OECI still provides the best forum for the directors of member institutes to meet regularly, to exchange views, and to formulate plans for future, inter-institutional collaborative ventures. It provides the right setting and the appropriate note of informality to overcome the political or cultural barriers, which sometimes risk frustrating the true and universal working relationship amongst the main players of the European cancer community. In the OECI Statute (Article 4 “Object”) the following is postulated: “The ultimate objective is the development of oncology in Europe for reducing mortality and morbidity due to cancer and increasing survival and quality of life of the patients. Therefore, the model of oncology must be based on a global vision of the cancer problem emphasizing the integration of research and education with diagnosis, prevention and care to promote the development of comprehensive and multidisciplinary organization within the European Cancer Institutes. With a view to simplifying and developing the scientiﬁc, educational and economic activities of its Members, to improving the conditions and increasing the outcomes, the object of the Grouping is mainly: the information, the formation, the research, the treatment, the care, the rehabilitation, the drafting of guidelines, the storage and evaluation of data, the costs beneﬁt, the clinical and preclinical research, the telemedicine and telematics, the education, the communication, the accreditation, the “labelisation” (marking), the translational research, the epidemiology and the ethical and social aspects in the cancer area”. During the last General Assembly, the OECI members approved to launch the European Cancer Mission Working Party aimed to discuss on how the OECI may participate to the incoming Horizon 2021–2027 Europe Framework Programme, where a small number of “Missions” with specific goals will be launched establishing a comprehensive portfolio of projects. The objectives of the Missions are to galvanise the EU Research and Innovation investment attracting funds from Member States and private investors, whilst taking into consideration the interests of the specific sectors and the sustainability of the actions: providing a direction for such investments is what a mission-oriented policy is about. The Missions will be decided and co-designed as part of a strategic planning process, which will include a collaborative effort amongst Commission departments, Member States, the European Parliament and relevant stakeholders. The OECI considers mandatory fostering innovation on primary and secondary prevention, so as to reduce morbidity and give health systems more possibility to support the increasing costs of care. Specific items are already selected, namely: Incidence and Prevalence; Primary prevention; Basic research; Molecular pathology and precision medicine; Translational research; Outcomes cancer research; Patient involvement; Quality and Organisation of a Cancer Centre; Health economics; Training. Listed above issues may constitute the basic elements of the Working Party and Project for a Cancer Mission. On November 21–22, 2019, the IEPOR under the OECI patronage will hold the 2nd International Conference “Tumor and Host: Novel Aspects of Old Problem” dated to the 25th anniversary of the Institute’s OECI membership, in which the representatives of the OECI Board as well as leading professionals from several European Cancer Institutes will take part along with the Ukrainian oncologists.